The Impact of Human Resource Information System Utilization on Human Resource Management Effectiveness: Evidence from Sinar Muslim Furniture Soppeng - A Nazalia Ramadhani We Tenripada; Andi Nurul Aksa (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
The development of information technology has encouraged organizations to improve human resource management (HRM) effectiveness through integrated information systems. One of the most widely adopted systems is the Human Resource Information System (HRIS), which supports employee data management, administrative efficiency, and managerial decision-making. This study aims to analyze the impact of HRIS utilization on HRM effectiveness at Sinar Muslim Furniture Soppeng. A descriptive quantitative approach was employed, involving all employees as respondents through a saturated sampling technique. Data were collected using questionnaires, interviews, and documentation, and were analyzed through descriptive statistics and simple linear regression. The findings indicate that HRIS utilization in the company is categorized as high (mean = 4.12), while HRM effectiveness is also high (mean = 4.11). Regression results show that HRIS utilization has a positive and significant effect on HRM effectiveness (B = 0.684; p < 0.05), with a coefficient of determination of 52%. These results confirm that HRIS plays a crucial role in enhancing HRM effectiveness through improved administrative accuracy, efficiency, and faster decision-making. Organizations are therefore encouraged to optimize HRIS implementation not only for administrative purposes but also for strategic HR development